Intracranial arterial variations and their relation with cerebral aneurysms: Analysis of 640 patients - Ahmet Uyanik, Sadik; Uzuncakmak Uyanik, Handan; Oguslu, Umut; Dede, Dogan (Annals of Medical Research, 2021)
Aim: To evaluate prevalence of cerebral arterial variations in Turkish population and association of the variations with cerebral aneurysmsMaterials and Methods: Digital subtraction angiography of 640 consecutive patients between January 2011-December 2013 were evaluated retrospectively. Patients with aneurysms were compared with patients without aneurysm to determine the effect of variations. Comparisons were made using Chi square or Fisher exact test for categorical variables and Student's t test or Mann Whitney U test for continuous variables.Results: The most common variation in the anterior circulation was hypoplasia of anterior cerebral artery A1 segment and the most common variation in the posterior circulation was fetal origin of the posterior cerebral artery. Hypoplasia and aplasia of the anterior cerebral artery A1 segment was significantly more frequent in patients with anterior communicating artery aneurysms than the control group (p:0.001). Prevalence of azygos anterior cerebral artery variation was higher in distal anterior cerebral artery aneurysms than the control group (p 0.001). There was no association between bihemispheric anterior cerebral artery and anterior communicating artery aneurysms (p = 0.453). Similarly, no significant association of fetal origin of posterior cerebral artery with posterior communicating artery aneurysms was found (p = 0.133). Conclusion: Prevalence of cerebral arterial variations in this study were compatible with literature. Some variations may play a role in development of aneurysms by alterations in hemodynamics and increasing shear wall stress. Further larger studies are needed to clarify the relation between variations in cerebrovascular structure and aneurysm formation.
Keywords: Aneurysm; angiography; intracranial; variation